Poverty rate determinants in the Central and Eastern Europe Member States - Maria-Daniela Tudorache (Theoretical and Applied Economics, 2019)
This paper aims to provide an analysis of the determinants of poverty rate in ten Member States of the European Union from the Central and Eastern Europe, and of the way how its influenced poverty in the 2009-2016 period. In order to estimate the impact, I used panel technique and Estimated Generalized Least Squares method with no effects, weighted by Period SUR option to provide more consistent estimators. To verify if the model is correctly specified and to confirm the maximum verisimilitude of the estimators, I tested the Gauss-Markov. The conclusion of the paper is that the unemployment rate, rural population, as well as the early leavers rate of people aged between 18-24, have a positive impact on the rate of people at risk of poverty rate after social transfers. On the other hand, the government spending on social protection has a negative impact on the used dependent variable.
Keywords: C23; G01; G31; O47; 330; poverty; panel; unemployment rate; rural; early leavers rate